LP-15 Decoding the Urban Exposome: Integrative Statistical Modelling of Epigenetic, Oxidative, and Genotoxic Biomarkers in Response to Air Pollution - Matković, K.; Jakovljević, I.; Davila, S.; Milić, M.; Kašuba, V.; Pehnec, G.; Kazensky, L.; Domijan, A.-M.; Bočkor, V. Vičić; Lukšić, F.; Zoldoš, V.; Cvetković, Ž.; et al. (Toxicology letters, 2025)
Urban air pollution, even at moderate levels, can induce early biological changes relevant to respiratory and systemic health. This study investigated the impacts of ambient air pollution on oxidative stress, immune regulation, and DNA damage in healthy adults in Zagreb, Croatia. A combination of advanced statistical methods – including best subset regression, hierarchical clustering, and mediation modelling – was applied to explore complex exposure–response relationships. Air quality data from fixed monitoring stations were used to construct multi-pollutant composite clusters, which were then linked to biomarkers of effect. A major finding from the statistical mediation modelling was a novel epigenetic mediation pathway in which FOXP3 gene methylation partially explains the association between pollen exposure and elevated fractional exhaled nitric oxide levels, suggesting that pollen may influence airway inflammation by modulating regulatory T-cell function. This suggests an immunological feedback mechanism linking allergen exposure to inflammation and immune modulation. Oxidative stress was explored through seven biomarkers, grouped into mainly pro-oxidant (superoxide dismutase, nitric oxide, reactive oxygen species, malondialdehyde) and antioxidant (glutathione, catalase, glutathione peroxidase) clusters. The pro-oxidant group was significantly associated with traffic- and combustion-related pollutants cluster (particulate matter (PM), polyaromatic hydrocarbons, volatile organic compounds, etc.), highlighting pollutant-induced redox imbalance. Individual factors such as physical activity and sex (male/female) further modified oxidative responses, illustrating the added value of multi-variable modelling in detecting subtle environmental effects. DNA damage endpoints were assessed using the comet and micronucleus assays. While DNA strand breaks measured by comet tail intensity were generally low, significant predictors included smoking status and certain pollutant clusters, particularly PM-bound metals exposures. However, no mediation via oxidative stress was observed for DNA damage, likely due to the relatively low – mostly within the proposed EU Directive for daily PM2.5 concentrations (25 µg/m3) – levels of air pollution and corresponding biological response. By integrating environmental and biomarker data with robust statistical tools, this study highlights the potential of advanced human biomonitoring approaches to detect early biological signals of air pollution exposure, even in urban settings with declining air pollution levels. Supported by the Croatian Science Foundation (#1192 HUMNap). Pollen data were obtained from the official pollen monitoring program managed by the Teaching Institute of Public Health “Dr. Andrija Štampar, with funding provided by the Zagreb City Office for Social Protection, Health, War Veterans and People with Disabilities.